Experience at the edge: Immediate experience and the given in twentieth-century Anglo-American philosophy. - Fortier, Evlyn. (University of Ottawa (Canada), 1999)
This thesis is an exploration of the idea of immediate experience. Three questions are asked: is there Immediate experience, what is immediate experience and what use is immediate experience. These questions are posed in the course of surveying the recent history of immediate experience with a view to rehabilitating it as a means of solving a particular philosophical problem. This problem is the paradox resulting from the fact that knowledge both depends on a dichotomy of 'knowing' and 'object known' (mind and world) and yet is vitiated by it. A synopsis of approaches to the problem of the dichotomy of mind and world is presented and claims about experience in relation to the paradox are examined. Then it is proposed that we should reconsider the theory of immediate experience, incorporating the idea that experience is already conceptually informed. This results in a theory of immediate experience that is conceptualizable, that is constituted of thinkable contents Immediate experience avoids the problems of dualism because it does not involve a dichotomy of mind and world. But once experience is conceptualized into ordinary, discursive experience, it involves a dichotomy so that knowledge is 'knowledge about.' By dissolving the paradox, immediate experience offers a better explanation than a dualistic account. And since immediate experience is conceptualizable, we avoid the criticism that there is no experience without interpretation or a conceptual framework in place.
Keywords: Philosophy.